2020
DOI: 10.1093/humupd/dmaa046
|View full text |Cite
|
Sign up to set email alerts
|

The other face of advanced paternal age: a scoping review of its terminological, social, public health, psychological, ethical and regulatory aspects

Abstract: BACKGROUND There is a global tendency for parents to conceive children later in life. The maternal dimension of the postponement transition has been thoroughly studied, but interest in the paternal side is more recent. For the moment, most literature reviews on the topic have focused on the consequences of advanced paternal age (APA) on fertility, pregnancy and the health of the child. OBJECTIVE AND RATIONALE The present revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 178 publications
1
10
0
Order By: Relevance
“…Since a consensus on the definition of advanced PatAGE remains lacking (Couture, Delisle, Mercier, & Pennings, 2021), in this study we treated PatAGE as a continuous variable rather than separating children into different groups. To examine the relationship between PatAGE and reading, we first calculated the zero‐order correlation.…”
Section: Methodsmentioning
confidence: 99%
“…Since a consensus on the definition of advanced PatAGE remains lacking (Couture, Delisle, Mercier, & Pennings, 2021), in this study we treated PatAGE as a continuous variable rather than separating children into different groups. To examine the relationship between PatAGE and reading, we first calculated the zero‐order correlation.…”
Section: Methodsmentioning
confidence: 99%
“…APA is associated with increased use of ART ( Bertoncelli Tanaka et al , 2019 ; American Society for Reproductive Medicine, Society for Assisted Reproductive Technology, 2017) due to a significant decrease in age-related female fertility for a couple and the slightly decreased male fertility, and because ART is considered generally safe. A father’s age for ART is rarely regulated in guidelines, except in Germany, where the age limit for ART is 50 years ( Belaisch-Allart et al , 2016 ; Couture et al , 2021 ). ART spans the periconception period from gametogenesis, fertilization and early embryonic development, coinciding with an intense epigenetic reprogramming in germ cells.…”
Section: Age Art Procedures and Additional Epigenetic Risksmentioning
confidence: 99%
“…In the past decade, data accumulating from epidemiological studies showed that the paternal age at conception is associated with an increased risk of de novo mutations ( Smits et al , 2022 , reviewed in Goldmann et al , 2019 ), which have significant effects on pregnancy outcomes and offspring health ( Belloc et al , 2014 ; Sharma et al , 2015 ; Khandwala et al , 2018 ). As noted in recent reviews ( Brandt et al , 2019 ; Couture et al , 2021 ), there is no consensus for the definition of advanced paternal age (APA), although some professional societies define APA as greater than 40 years of age.…”
Section: Introductionmentioning
confidence: 99%
“…Since a consensus on the definition of advanced paternal age remained lacking (Couture, Delisle, Mercier, & Pennings, 2020), in this study we treated PatAGE as a continuous variable rather than separating children into different PatAGE groups. To examine the relationship between PatAGE and reading, we first calculated the zero-order correlation between them.…”
Section: Behavior Analysesmentioning
confidence: 99%